2018
DOI: 10.1111/corg.12260
|View full text |Cite
|
Sign up to set email alerts
|

Equity crowdfunding in Germany and the United Kingdom: Follow‐up funding and firm failure

Abstract: Manuscript type Empirical Research question/issue Today, startups frequently obtain financing via the Internet through many small contributions of nonsophisticated investors. Yet, little is known whether these startups can ultimately build enduring businesses. This study investigates the determinants of follow‐up funding and firm failure after an equity crowdfunding campaign has taken place. Research findings/insights We use hand‐collected data from 13 different equity crowdfunding portals and 413 firms that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 82 publications
6
41
0
1
Order By: Relevance
“…Walthoff-Borm et al (2018) compare the financial performances of firms that received equity crowdfunding with matched firms that did not receive such funding; firms that received equity crowdfunding exhibit lower financial performances and have considerably higher failure rates. A similar result is shown by Hornuf et al (2018) who demonstrate that the hazard of firm failure increases with the valuation of the firm, but decreases with the amount raised during the crowdfunding campaign. Hornuf et al (2018) also found that firms who received equity crowdfunding registered a higher chance of obtaining follow-up funding through business angels or venture capitalists.…”
Section: Theorethical Backgroundsupporting
confidence: 79%
See 1 more Smart Citation
“…Walthoff-Borm et al (2018) compare the financial performances of firms that received equity crowdfunding with matched firms that did not receive such funding; firms that received equity crowdfunding exhibit lower financial performances and have considerably higher failure rates. A similar result is shown by Hornuf et al (2018) who demonstrate that the hazard of firm failure increases with the valuation of the firm, but decreases with the amount raised during the crowdfunding campaign. Hornuf et al (2018) also found that firms who received equity crowdfunding registered a higher chance of obtaining follow-up funding through business angels or venture capitalists.…”
Section: Theorethical Backgroundsupporting
confidence: 79%
“…A similar result is shown by Hornuf et al (2018) who demonstrate that the hazard of firm failure increases with the valuation of the firm, but decreases with the amount raised during the crowdfunding campaign. Hornuf et al (2018) also found that firms who received equity crowdfunding registered a higher chance of obtaining follow-up funding through business angels or venture capitalists.…”
Section: Theorethical Backgroundsupporting
confidence: 79%
“…only bridge the funding gap for the entrepreneurial ventures or social projects (Polzin et al, 2018) but also build customer awareness, receive feedback, and develop credibility with other potential investors (e.g., Belleflamme et al, 2014Belleflamme et al, , 2015Colombo et al, 2015;Crosetto & Regner, 2018;Hornuf et al, 2018;Mollick, 2016;Stanko & Henard, 2017). Also, considering the burgeoning demand for crowdfunding (Crosetto & Regner, 2018;Rey-Martí et al, 2019), there is a substantial need for new backers contributing to crowdfunding campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…A different study examining 413 equity funded firms in Germany and the UK (Hornuf et al 2018) found that overall 77 firms (18.8%) successfully raised follow-up funding after the latest equity crowdfunding campaign, and 69 firms (16.7%) went insolvent, were liquidated, or were dissolved. Furthermore, the study showed that, in comparison to UK firms, equity crowdfunded German firms stood a higher chance of raising follow-up funding from business angels or venture capital, but also had a higher likelihood of failure.…”
Section: Outcomes Of Crowdfunding In Europementioning
confidence: 99%